2017
DOI: 10.1002/anie.201611049
|View full text |Cite
|
Sign up to set email alerts
|

Thermally Adjustable Dynamic Disulfide Linkages Mediated by Highly Air‐Stable 2,2,6,6‐Tetramethylpiperidine‐1‐sulfanyl (TEMPS) Radicals

Abstract: Intrinsically exchangeable dynamic covalent bonds that can be triggered by readily usable stimuli offer easy incorporation of their dynamic properties in various molecular systems, but the library of such bonds is still being developed. Herein, we report the dynamic covalent chemistry of 2,2,6,6-tetramethylpiperidine-1-sulfanyl (TEMPS) dimers derived from thermally reversible homolytic dissociation of disulfide linkages. High air stability of TEMPS was observed even at 100 °C, affording facile employment of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

11
110
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 99 publications
(121 citation statements)
references
References 51 publications
11
110
0
Order By: Relevance
“…We have previously reported that the BiTEMPS unit behaves as a stable covalently bound structure at room temperature, while it exchanges disulfide bonds above 80 8C. [37] We have also demonstrated that a solution of polyurethanes containing BiTEMPS units in the polymer repeating units undergo an entropy-driven transformation from linear polymers to oligomers under high dilution conditions, which can be reversed under concentrated conditions upon heating. This finding inspired us to develop a strategy toward compounds with a cyclic topology since the main oligomer structures obtained by entropy-driven transformations (mainly translational entropy of cyclic oligomers and polymer are both greatest at high dilution, while both decrease as the concentration increase) should be cyclic given the recombination of dynamic covalent bonds and the small number of terminal structures on the polymer chain.…”
mentioning
confidence: 79%
See 2 more Smart Citations
“…We have previously reported that the BiTEMPS unit behaves as a stable covalently bound structure at room temperature, while it exchanges disulfide bonds above 80 8C. [37] We have also demonstrated that a solution of polyurethanes containing BiTEMPS units in the polymer repeating units undergo an entropy-driven transformation from linear polymers to oligomers under high dilution conditions, which can be reversed under concentrated conditions upon heating. This finding inspired us to develop a strategy toward compounds with a cyclic topology since the main oligomer structures obtained by entropy-driven transformations (mainly translational entropy of cyclic oligomers and polymer are both greatest at high dilution, while both decrease as the concentration increase) should be cyclic given the recombination of dynamic covalent bonds and the small number of terminal structures on the polymer chain.…”
mentioning
confidence: 79%
“…Considering that a cyclization process is inevitable at some point during the synthesis of compounds with a cyclic topology and that this step is presumably the most difficult, we thought that using a spontaneous and selective cyclization would be ideal. In this work, we focus on the dynamic covalent chemistry [34][35][36] of bis(2,2,6,6-tetramethylpiperidin-1yl)disulfide (BiTEMPS) [37] and use it as the driving force to induce an ideal cyclization. We have previously reported that the BiTEMPS unit behaves as a stable covalently bound structure at room temperature, while it exchanges disulfide bonds above 80 8C.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Considering that a cyclization process is inevitable at some point during the synthesis of compounds with a cyclic topology and that this step is presumably the most difficult, we thought that using a spontaneous and selective cyclization would be ideal. In this work, we focus on the dynamic covalent chemistry of bis(2,2,6,6‐tetramethylpiperidin‐1‐yl)disulfide (BiTEMPS) and use it as the driving force to induce an ideal cyclization. We have previously reported that the BiTEMPS unit behaves as a stable covalently bound structure at room temperature, while it exchanges disulfide bonds above 80 °C .…”
Section: Figurementioning
confidence: 99%
“…In this work, we focus on the dynamic covalent chemistry of bis(2,2,6,6‐tetramethylpiperidin‐1‐yl)disulfide (BiTEMPS) and use it as the driving force to induce an ideal cyclization. We have previously reported that the BiTEMPS unit behaves as a stable covalently bound structure at room temperature, while it exchanges disulfide bonds above 80 °C . We have also demonstrated that a solution of polyurethanes containing BiTEMPS units in the polymer repeating units undergo an entropy‐driven transformation from linear polymers to oligomers under high dilution conditions, which can be reversed under concentrated conditions upon heating.…”
Section: Figurementioning
confidence: 99%